Geometry of Centroaffine Surfaces in R⁵ - Bushek, N.; Clelland, J.N. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We use Cartan's method of moving frames to compute a complete set of local invariants for nondegenerate, 2-dimensional centroaffine surfaces in R⁵∖{0} with nondegenerate centroaffine metric. We then give a complete classification of all homogeneous centroaffine surfaces in this class.